The leadership challenge - Kouzes, James M.; Posner, Barry Z. (The Jossey-Bass management series, 2007)
With an expanded research base of sixty thousand leaders and constituents, this new edition of The Leadership Challenge captures the continuing interest in leadership as a critical aspect of human organizations. It offers a broader scope for viewing leaders in every industry and all walks of life, including the education and nonprofit fields.